Potential impact of the European Green Agreement on EU and Hungarian crop production - Szabó, Levente; Madai, Hajnalka; Nábrádi, András (Applied Studies in Agribusiness and Commerce, 2022)
European arable farming, including Hungarian arable farming, faces a huge dilemma: how to contribute to and maintain the global food supply while reducing greenhouse gas emissions while main taining biodiversity, but reducing inputs that are potentially damaging to society and the environment while ensuring that no more land is taken out of production? Not to mention that the increasingly urgent need to tackle climate change is also placing additional demands on EU agricultural decision-makers. Under the European Green Deal (GD), the 'From Farm to Fork' (F2F) strategy will help achieve climate neutrality by 2050, with a target of a 55% reduction in greenhouse gas emissions by 2030. Achieving this will require significant changes in food production, a shift in crop health strategies and accelerated innovation in the agricultural sector. The study addresses these issues. Our first hypothesis (A1) is that the GD and F2F strategies can be implemented without problems and without losses. Our second assumption (A2) is that the know-how solutions and the technological conditions for precision agriculture that are already available exist, and that all of these already justify the feasibility of A1. In order to prove this, we have reviewed recent and up-to-date literature on DG and F2F. For A1, we found that there are pro and con findings in the literature. However, the summary finding is not positive. The conclusion of the studies, based on data calculations, is that EU agriculture faces huge additional costs if it is to maintain production and reduce environmental pressures. Their calculations suggest that more people will be disadvantaged by the decisions, and that millions of euros could be lost to the public. However, the article also shows that there are many cases where positive results can be achieved even with reduced chemical use. Facts and figures from international and Hungarian technological and know-how solutions and their trials at plant level show that the DG's objectives are already partially achievable. It has been established that the systematic use of precision technologies allows to increase the natural and at the same time the economic efficiency. In our work we have used the results of primary and recent secondary research. We have shown the downsides of GD, but also that with targeted support, the objectives of sustainability and GD can be approached. Changes in 2022, drastic price increases for inputs including fertilizers and pesticides, inflation at a 20-year high, energy prices spiraling out of control, and an almost unprecedented drought affecting crop production and horticulture, point to the need for a radical change in technology, thinking and regulation. And all this to ensure that there is enough affordable food in Hungary, that there are export products within and outside the Community, and that those working in agriculture have a decent living.